2006
DOI: 10.3748/wjg.v12.i43.7007
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer screening by non-invasive metabolic biomarker fecal tumor M2-PK

Abstract: Fecal tumor M2-PK is an appropriately sensitive tool to pre-select those patients requiring colonoscopy for the further diagnostic confirmation or exclusion of colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
48
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 27 publications
8
48
2
Order By: Relevance
“…The finding that faecal tumour M2 PK levels are not markedly increased in subjects with colorectal adenomas is in contrast to the much higher overall sensitivity that has been reported for invasive CRC, but it is consistent with the stage-dependent performance of this test observed for CRC: all pertinent studies reported notably higher sensitivity for more advanced CRC than for less advanced CRC (Hardt et al, 2004;Tonus et al, 2006;Haug et al, 2007;Mulder et al, 2007;Koss et al, 2008). This suggests that in the precancerous phase, the critical stage of neoplasia leading to increased faecal tumour M2 PK levels may not be reached yet.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The finding that faecal tumour M2 PK levels are not markedly increased in subjects with colorectal adenomas is in contrast to the much higher overall sensitivity that has been reported for invasive CRC, but it is consistent with the stage-dependent performance of this test observed for CRC: all pertinent studies reported notably higher sensitivity for more advanced CRC than for less advanced CRC (Hardt et al, 2004;Tonus et al, 2006;Haug et al, 2007;Mulder et al, 2007;Koss et al, 2008). This suggests that in the precancerous phase, the critical stage of neoplasia leading to increased faecal tumour M2 PK levels may not be reached yet.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies investigating this test reported a comparably high sensitivity for CRC ranging about 70 -80%, whereas specificity ranged about 70 -90% (Hardt et al, 2004;Vogel et al, 2005;Shastri et al, 2006;Tonus et al, 2006;Haug et al, 2007;Mulder et al, 2007;Koss et al, 2008). However, the potential of the tumour M2 PK test to detect colorectal adenomas, an issue that is highly relevant for estimating its use in reducing CRC incidence and mortality, has been investigated rarely and with rather limited sample size only (Vogel et al, 2005;Shastri et al, 2006;Mulder et al, 2007;Koss et al, 2008).…”
mentioning
confidence: 99%
“…In 2010, a meta-analysis reported a sensitivity (67%) and specificity (8 %) for immunological FOBt compared with 54% and 80% for g-FOBt, for the detection of colorectal cancer and pre-cancerous neoplasia [7]. The low sensitivity of g-FOBt has led to criticism of its use for population-based screening [9].…”
Section: Introductionmentioning
confidence: 99%
“…An alternative faecal-based screening tool is tumour M2-pyruvate kinase (tM2-PK) [9,10]. tM2-PK is an isoenzyme of pyruvate kinase; it is involved in glycolysis and catalyzes the ATP-producing conversion of phosphoenolpyruvate to pyruvate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation